Prevalensi bottle feeding caries dan faktor risiko pada anak usia 3 sampai 5 tahun di Wilayah Kerja Puskesmas Mengwi III Badung - Made Dena Pramita; L W Ayu Rahaswanti; Ni Luh Putu Ariastuti (Bali Dental Journal, 2019)
Introduction: Bottle feeding caries is multifactorial tooth decay in infants due to the high consumption of refined carbohydrates, and poor oral hygiene. Risk factors for bottle feeding caries include parent socio-economic status, knowledge of parents, experience of dental caries of parents, certain diseases, and the habit of drinking poor formula milk.The aim of the study is to investigate the prevalence and risk factor of bottle feeding caries in children aged 3 to 5 years old at Puskesmas Mengwi III Badung work area. Method: This study is a cross sectional observational descriptive study, and used multistage random sampling technique on 93 children aged 3 to 5 years old. Result: The prevalence of of bottle feeding caries was 40.9%, and the incidence of bottle feeding caries had tendency to happen in children aged 3 to 5 years old who had her/his first tooth eruption at the age of 8 to 12 month, and had poor pattern of bottle feeding. Conclusion: The conclusion of this study is the prevalence of bottle feeding caries in Puskesmas Mengwi III Badung work area is relatively high. Most of those children came from poor socio-economic family, parents with caries history and have low level of knowledge about oral hygiene maintenance.